Analysis of the Implementation of the Istishna' Agreement on Sharia Housing in Palima Grand City, Serang, Indonesia - Mustori Mustori; Rohmani Rohmani (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2022)
This study aims to dig deeper into the implementation of the istishna contract in Palima Grand City sharia housing. This research uses descriptive qualitative method. Primary data sources come from important documents of Palima Grand City as well as answers from related parties interviewed. While secondary sources from various scientific references related to the discussion. This study shows that Palima Grand City is a sharia housing that is engaged in the developer sector, always providing housing with a comfortable, safe, Islamic nuanced concept, and in accordance with sharia principles. The contract used in buying and selling houses in Palima Grand City sharia housing is the bai' istishna contract scheme. There are four payment mechanisms offered by the developer to the customer, namely, prepayment, payment upon delivery of goods, payment during the house-building process, and deferred payment for a certain time. The transaction of buying and selling houses in Palima Grand City sharia housing does not use the services of a bank as a third party, so there is no BI Chaking.